Modelación numérica del comportamiento de la presa del proyecto hidroeléctrico El Guavio (2015)
This work represents the numerical modeling using finite element software , which performed the behavior of the dam Alberto Lleras , in the hydroelectric project Guavio where a coupled development between stress-strain analysis and liquid flow is considered ( water ) in the porous medium . The modeling took into account the different circumstances of geometry and loads during the process of construction of the dam by ascending stages , as in his time waiting for the initial filling (about 3 years), during the first filling and , Finally , the operating period for the generation of electricity. To approach the behavior of the two main materials that are part of the dam : Core clay and riprap , mechanical models Modified Cam Clay (MCC ) and linear elastic, respectively were adopted.